Prioritization of river basins in the Tshwane area with reference to faecal coliform bacteris for the purpose of the identification of candidate wetlands for rehabilitation - Venter, Adri (My University, 2008)
Wetlands are considered a last line of defence against poor water quality. Despite the natural capabilities of wetlands to remove a variety of contaminants from surface water, the track record for wetland conservation leaves much to be desired. In the northern parts of the City of Tshwane, 84% of wetlands have been degraded. When viewed against the poor bacteriological quality of river water in the study area, the lack of wetland conservation efforts is of particular concern. Given the large number of wetlands in the Tshwane area in need of rehabilitation, this study aimed to devise a methodology to prioritise these wetlands for rehabilitation. No blueprint for such a prioritisation process exists, as studies are adapted to take into account the availability of data and the unique requirements of the study area. The methodology for this study is based on the prioritisation of a specific river basin, based on expected maximum faecal bacterial load originating from various sources of pollution. Four river basins were compared with each other in a series of screening processes. Screening was done on a landscape level using a Geographic Information System (GIS) to generate various composite layers as part of the screening process. The screening processes relied on the application of several weighted criteria. Weights for criteria are based on scientific literature. Weights are also allocated in line with the “worst case scenario”, as the study is in essence an assessment of the various pollution sources and their maximum possible contribution to deteriorating surface water quality. A Simple Additive Weighting technique was used to assess the total pollution loads and total numbers of users at risk from contaminated surface water in each of the river basins. It is important to note that the objective is to only rate the pollution sources, whilst exact pollution loads were not calculated. Diffuse, areal and point sources of pollution were rated using the estimated contributions to faecal coliform loads. The river basin with the highest score was selected for the selection of candidate wetlands for rehabilitation purposes. The Apies River Basin scored highest for most of the criteria, with the exception of the number of households at risk from contaminated surface water. Despite the 0.60 weight allocated to households at risk, the extent of pollution sources in this river basin allowed it to be singled out as the basin in which a wetland for rehabilitation is most urgent in order to attenuate bacterial load. Two wetlands were short listed, based on their high need for rehabilitation, their hydrogeomorphic location (valley bottom with a channel), and given that they are larger than 1ha in size and within a minimum distance from the households at risk. Site level assessments are required for a final selection between the two, taking into account the nature of the current disturbances, the possibility of risk due to back-flooding, the projected costs associated with rehabilitation, the nature of the vegetation associated with the wetlands and the general conservation value of each of the wetlands.
Keywords: water resource management; catchment; river basin; wetlands; water pollution; faecal coliform